Making a Connection between Knowledge-Based Economy and New of Knowledges in Developing Arabic Language Discipline Jobs - سعيد سواري; د. عبد الله حسيني (Thi Qar Arts Journal, 2021)
Job increase in the present economy is dependent on knowledge-based economy because it has a great effect on developing jobs. Therefore, present study, by employing a descriptive-analytical method, aims to study the role of connection between Arabic language and new knowledges in developing jobs related to Arabic language; the focus is not solely on teaching and translation, rather on other well-paid jobs like marketing, religious and medical tourism, management and counseling in tourism industry and hotels. However, students majoring in Arabic discipline can benefit from being employed in these new jobs only if they have sufficient knowledge of Internet, communication, computer programs, and marketing and advertising industry. Making a connection between Arabic discipline and new knowledges and developing jobs and learning new knowledges by Arabic students and graduates require the establishment of knowledge-based institutes, so that they can be trained on the basis of new pedagogical methods and scientific and technological courses. Afterwards, they can be connected to governmental and privates institutes of job development to prepare them for national and international markets. Thus, in this study, it is believed that connecting Arabic language with knowledge-based economy and new knowledges increases the jobs for the graduates. It is worth noting that this topic of has never been explored in Arabic language context